Rationale and protocol for a safety, tolerability and feasibility randomized, parallel arm, double-blind, placebo-controlled, pilot study of a novel ketone ester targeting frailty via immunometabolic geroscience mechanisms. - Brianna J Stubbs; Gabriela Alvarez Azañedo; Sawyer Peralta; Stephanie Roa Diaz; Wyatt Gray; Laura Alexander; Wendie Silverman-Martin; Thelma Y Garcia; Traci M Blonquist; Vaibhav Upadhyay; Peter J Turnbaugh; James B Johnson; et al. (PLoS ONE, 2024)
Background Frailty is a geriatric syndrome characterized by chronic inflammation and metabolic insufficiency that creates vulnerability to poor outcomes with aging. We hypothesize that interventions which target common underlying mechanism of aging could ameliorate frailty. Ketone bodies are metabolites produced during fasting or on a ketogenic diet that have pleiotropic effects on inflammatory and metabolic aging pathways in laboratory animal models. Ketone esters (KEs) are compounds that induce ketosis without dietary changes, but KEs have not been studied in an older adult population. Our long-term goal is to examine if KEs modulate aging biology mechanisms and clinical outcomes relevant to frailty in older adults. Objectives The primary objective of this randomized, placebo-controlled, double-blinded, parallel-group, pilot trial is to determine tolerability of 12-weeks of KE ingestion in a broad population of older adults (≥ 65 years). Secondary outcomes include safety and acute blood ketone kinetics. Exploratory outcomes include physical function, cognitive function, quality of life, aging biomarkers and inflammatory measures. Methods Community-dwelling adults who are independent in activities of daily living, with no unstable acute medical conditions (n = 30) will be recruited. The study intervention is a KE or a taste, appearance, and calorie matched placebo beverage. Initially, acute 4-hour ketone kinetics after 12.5g or 25g of KE consumption will be assessed. After collection of baseline safety, functional, and biological measurements, subjects will randomly be allocated to consume KE 25g or placebo once daily for 12-weeks. Questionnaires will assess tolerability daily for 2-weeks, and then via phone interview at bi-monthly intervals. Safety assessments will be repeated at week 4. All measures will be repeated at week 12. Conclusion This study will evaluate feasibility, tolerability, and safety of KE consumption in older adults and provide exploratory data across a range of aging-related endpoints. This data will inform design of larger trials to rigorously test KE effects on aging mechanisms and clinical outcomes relevant to frailty.